Some aspects of social change in a cretan mountain village - Saulnier, Francoise (The Greek Review of Social Research, 1981)
The first part of the article presents the traditional village organiza tion studying some socio-economic aspects whose dynamic nàture is underlined. The most recent developments in the village are after wards dealt with, first on the economic level with the influence of tourism, then on the social level with the reinforced autonomy of the marital cell in regard to kinship and individualization of the people vis-à-vis the family group. The opposition between traditional and contemporary societies was only established for purposes of clarity because there is no rupture between the two.